Designing electronic systems for EMC - Duff, William G. (The SciTech series on electromagnetic compatibility, 2011)
This book reviews developments in the following topics: electronic system design; EMC; shielding theory; protection technique; bonding; grounding; filter; ferrite; isolator; transient suppressor; cable; and connector.